Peningkatan Daya Saing Kuliner Umkm Melalui Pengemasan Produk - Shinta Utiya Syah (Badań Perencanaan Pembangunan Dearth, Penelitian dań Pengembangan Provinsi Riau, 2017)
Packaging has an important role in preservation or in maintaining the quality of food products and agricultural products. Packing can help prevent and protect products from the comfort of physical damage and the intensity of pollution. Currently, packaging is growing rapidly along with the rapid development of industries that use it and various materials and packaging forms are widely available and can easily be obtained on the market in accordance with the needs. This study aims to determine the best packaging type to muti some culinary products of UMKM in Riau Province. In this research primary data collection with questionnaire distribution and selected 26 culinary producer as sample. The average age of culinary producers is 41-50 years, female sex (80.5%) and married (88.5%), high school education (61.5%), duration less than 5 years (67 , 3%) with monthly income less than 5 million (77%). Most (84%) of culinary products use plastic, most used plstik type is polyethylene with thickness 0,1 mm. From the results of organoleptic test of quality, type, and packaging of average culinary products are not favored by the disputants